Non-EFL Students' Ability in Writing Simple Sentences of Descriptive Paragraphs - Tira Nur Fitria (English Education Department at FKIP Nommensen University, 2022)
The objective of this study is to know the students’ ability in writing English simple sentences. This research is descriptive qualitative. The result shows that students have understanding of how to construct simple sentences in several formulas such as Subject + Verb + Complement (S + V + C), Subject + Verb + Adverb (S + V + Adv), Subject + Verb + Object (S + V + Object), and Subject + Verb + Object + Adverb (S + V + O + Adverb). But, besides using simple sentences, the students also still use other sentence forms to support information in their paragraphs such as 1) compound sentences by using the coordinating conjunction for example “so”, ”but”, and “and”. 2) complex sentence by using the coordinating conjunction for example “after”, “before”, “so that”, “if”, “that”, “because”, “even though”, “although”, “when, “while”. 3) compound-complex sentence by using both coordinating conjunction and subordinating conjunction”. Therefore, the teachers/lecturers need to give understanding more to the students that 1) a simple sentence has one independent clause and expresses one idea/topic. 2) simple sentence must have a subject-verb combination, but the subject can be compound or more than one. 3) simple sentence can have a compound verb. 4) simple sentences can only have one subject-verb combination and commas are not used. The students must be able to understand and know the subject, predicate (verb) and nouns, adjectives, and adverbs that will give a complete meaning. So that those who read will understand what they want to convey through the sentence.